2014
DOI: 10.7763/ijtef.2014.v5.416
|View full text |Cite
|
Sign up to set email alerts
|

Customer Satisfaction in Using e-Travel: The Role of Self Efficacy, Trust, and Use

Abstract: Abstract-the purpose of today business is not only the national business, but also the international business through e-business concept in particular e-travel contexts. E-travel is a tourism activity that done automatically through electronic technology and can be accessed from anywhere via its websites. The current paper presents to develop the conceptual framework of e-travel adoption model. Self-efficacy, trust and actual use are identified as influencing factors of customer satisfaction on e-travel. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Some authors have found that self-efficacy is positively associated with online travel purchases (Amaro & Duarte, 2015) and with the use of online travel websites (Joshua & Pujani, 2014). Similarly, efficacy has also been shown to be an important determinant of members' active contributions to an online travel community (Wang & Fesenmaier, 2003), and Lu, Mao, Wang, and Hu (2015) found that users with higher levels of self-efficacy in using travel apps tend to have higher expectations of the apps, which results in behavioural intentions to use them.…”
Section: Customer Engagement Behaviours and Their Determinantsmentioning
confidence: 99%
“…Some authors have found that self-efficacy is positively associated with online travel purchases (Amaro & Duarte, 2015) and with the use of online travel websites (Joshua & Pujani, 2014). Similarly, efficacy has also been shown to be an important determinant of members' active contributions to an online travel community (Wang & Fesenmaier, 2003), and Lu, Mao, Wang, and Hu (2015) found that users with higher levels of self-efficacy in using travel apps tend to have higher expectations of the apps, which results in behavioural intentions to use them.…”
Section: Customer Engagement Behaviours and Their Determinantsmentioning
confidence: 99%